Nutritional Education And Use Of Local Food For Mothers Of Toddlers In Preventing Stunting At 1000 HPK - Rosnah, Rosnah; Sarita, Sultina; Dali; Rofiqoh; La Banudi; Toruntju, Sultan Akbar (Jurnal Stunting Pesisir dan Aplikasinya, 2023)
Stunting is chronic malnutrition in toddlers resulting from a lack of nutritional intake for a long time and is usually accompanied by frequent illnesses. The target audience for this community service activity is 30 mothers of toddlers. The method used is health education in the form of counseling and interactive discussions. This activity was carried out on June 2 2022 at the Puuwonua Village Hall, working area of ??the Lalonggasu Meeto Community Health Center, Konawe Regency. The results of this community service activity showed that there was an increase in knowledge about nutrition after providing counseling to mothers of toddlers who had an average pre-test score of 6.0 which rose to 8.6 at post-test; The results of the analysis of different tests showed that there was a difference in the mean knowledge scores of participants before and after counseling (p=0.000). Conclusion: implementing outreach to increase nutritional knowledge among mothers of toddlers has proven to be effective, especially in implementing balanced nutrition within 1000 HPK and using local food in efforts to prevent stunting.